Análise da punção e flechas em lajes maciças sem vigas de concreto armado de acordo com as prescrições da NBR 6118:2003 - Ferreira, Antônio Mário (Universidade Federal de São Carlos, 2005)
This work shows some NBR 6118:2003 prescriptions, intending to study, analyze and discuss the aspects regarding to the determination of the efforts to check the punch and the detailed framework to struggle it and the deflection (arrow), in the systems of flat plates since they had suffered significant changes. It will be done a comparative analysis of consideration of the non physical linearity presented by structural calculation program CYPECAD to that one done according to NBR 6118:2003, using a grill analogy through the GPLAN program to do that, as it will be also solved some examples to determine the strain and the framework structure to the punch as to deflection in the flat plates. At last, it will be done a study of case of a building in solid flat plates that presents deflection problems, as well as project failures in the dimension of the flat to punch, which subjects deserve a high attention and concern under the vision and sight of NBR 6118:2003. Specifically it will be dealt the following subjects: General features of the system; Methods to determine the strain and dimension to the punch; Verification of the deflection of the flat; Utilization of the programs to determine the strain and deflection; Performance and some examples and a study of the case.
Keywords: Engenharia de estruturas; Lajes sem vigas; Flecha; Punção; Flat plates; Punch; Deflection; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL